Detective Policing and the State in Nineteenth-century England: The Detective Department of the London Metropolitan Police, 1842-1878 - Griffin, Rachael (2015)
This thesis evaluates the development of surveillance-based undercover policing in Victorian England through an examination of the first centralized police detective force in the country, the Detective Department of the London Metropolitan Police (1842-1878). It argues that the Detective Department overcame British fears that detective police were incompatible with individual liberty and parliamentary democracy, making the English detective a familiar and reliable public servant. The Detective Department, which worked from Scotland Yard, was formed in 1842 in response to criticism that the Metropolitan Police was unable to successfully investigate homicide. This was a surprising development in a country where property crime had always spurred developments in criminal justice. London’s newspapers played a key role in the creation of this detective force by creating a murder scare and demanding that the Metropolitan Police devote more specialized attention to complicated investigations, including homicide. The new detective force remained small to protect the police from accusations of spying. Since murders were infrequent, the new detectives devoted most of their attention to property crime, especially theft. During the 1860s and the economically depressed 1870s, detective priorities reflected a government crackdown on forgery and fraud, crimes that threatened the paper economy upon which Britain’s industrial and mercantile power rested. Detectives also regularly worked for the Home Office to help supplement limited investigative machinery in the counties. Scotland Yard detectives routinely travelled throughout England helping local magistrates investigate felonies ranging from homicide to arson. Scotland Yard’s close relationship with the Home Office was unique in England and resulted from London’s lack of municipal authority. For this reason, Metropolitan Police detectives often acted as agents of the British government, especially when they monitored foreign nationals and refugees that arrived in England following European revolutions in 1830 and 1848. Detectives’ non-felony work for the Home Office, which also included evaluating naturalization applications and performing extraditions, offers a new perspective on Victorian detectives and their cases that is neglected in current historiography